2013
DOI: 10.1371/journal.ppat.1003508
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Native Agonist and Synthetic Inhibitor Recognition by the Pseudomonas aeruginosa Quorum Sensing Regulator PqsR (MvfR)

Abstract: Bacterial populations co-ordinate gene expression collectively through quorum sensing (QS), a cell-to-cell communication mechanism employing diffusible signal molecules. The LysR-type transcriptional regulator (LTTR) protein PqsR (MvfR) is a key component of alkyl-quinolone (AQ)-dependent QS in Pseudomonas aeruginosa. PqsR is activated by 2-alkyl-4-quinolones including the Pseudomonas quinolone signal (PQS; 2-heptyl-3-hydroxy-4(1H)-quinolone), its precursor 2-heptyl-4-hydroxyquinoline (HHQ) and their C9 congen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
305
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(323 citation statements)
references
References 53 publications
16
305
0
2
Order By: Relevance
“…Interference with the function of MvfR results in lowered virulence by P. aeruginosa (52,53). Consequently, MvfR has advanced to a target for the development of strategies to combat P. aeruginosa infections.…”
Section: Discussionmentioning
confidence: 99%
“…Interference with the function of MvfR results in lowered virulence by P. aeruginosa (52,53). Consequently, MvfR has advanced to a target for the development of strategies to combat P. aeruginosa infections.…”
Section: Discussionmentioning
confidence: 99%
“…However, both HHQ and PQS are coinducers of the virulence-associated LysR-type transcriptional regulator PqsR (41). The structural moieties that underpin the interaction between HHQ/PQS and PqsR remain to be fully characterized, although recent studies have reported diverse classes of PqsR antagonists (53)(54)(55) and implicated the hydrophobic pocket situated within the PqsR protein (56). Therefore, in order to assess whether the lead compounds could elicit a virulence response from P. aeruginosa, phenazine production and pqsA promoter activity (57) were monitored in a pqsA mutant where the capacity to produce native HHQ and PQS had been lost.…”
Section: Fig 3 Microscopic Analysis Reveals Altered Biofilm Structurementioning
confidence: 99%
“…We recently showed that another HAQ, 2-n-heptyl-4-hydroxyquinoline-N-oxide (HQNO), promotes biofilm formation and biofilm tolerance to antibiotics by inducing eDNA release that occurs as a result of autolysis due to self-poisoning of the respiratory chain by this molecule (14). A few studies have reported that inhibitors of PqsD or MvfR interfere with biofilm formation, but their antibiofilm potency was limited to the high micromolar range (11,(15)(16)(17). We recently described a benzamide-benzimidazole (BB) series of highly potent and cell-permeable inhibitors of MvfR (18).…”
mentioning
confidence: 99%